Analysis of the Degree of Use of Balanced Scorecard Metrics in Agro-industrial Companies Based on Strategic Goals - de Vasconcelos, Gabriela; Cunha Callado, Antônio André; Cunha Callado, Aldo Leonardo (Nexo Revista Científica, 2023)
The objective of the article is to analyze the degree of use of performance indicators associated with the four perspectives of the Balanced Scorecard considering different strategic goals in the context of agro-industrial companies. Samples of rural companies located in the State of Pernambuco have been investigated considering the adoption of strategic goals associated with innovation, improvement and continuity, carrying out the use of 48 performance indicators, classified from four perspectives of the Balanced Scorecard. The data was collected through surveys structured from a questionnaire. Two different statistical techniques were used to analyze the results: descriptive statistics and the Kruskal-Wallis test. The results obtained demonstrate the identification of traits regarding the group of performance indicators that have obtained high percentages of use in the three strategic goals tested. It was observed that the companies that adopt strategic goals regarding continuity, presented declared standards of use that are lower than those presented by companies that adopt strategic innovation and improvement goals. No statistically significant discrepancies were found regarding the intensity of use of the indicators of the Balanced Scorecard perspectives when the joint analysis of internal balance considering each of the strategic goals.